A budding case of infectious endocarditis: Candida lusitaniae. (2020) - Rahmati, Elham; Correa, Adrian J.; She, Rosemary C.
Abstract: This is a case of recurrent Candida lusitaniae prosthetic valve endocarditis with budding yeast and pseudohyphae on the histopathology. This case illustrates the importance of keeping vigilant in recognizing some of the emerging drug resistant Candida species in our practice.